Still foolin' 'em [compact disc, unabridged] : where i've been, where i'm going, and where the hell are my keys? - Crystal, Billy (Macmillan Audio, 2013)
Hilarious and heartfelt observations on aging from one of America's biggest movie stars as he turns 65, and a look back at a remarkable career.